Kepemimpinan Kepala Sekolah Dalam Memanajenen Bisnis Center SMK Sunan Drajat Lamongan - Juliyani, Erly (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2021)
The principal's leadership is very important for the sustainability of the school organization, including the business center unit. The school principal is the driving force of the economy to make the school independent in terms of financing. The aim of this research is to determine the extent of the principal's leadership role in managing the business center of Sunan Drajat Lamongan Vocational School. The method used is a qualitative research method based on phenomenology. The results of this research are that school principals must have a good entrepreneurial spirit to be able to manage school business units and must have good management to be able to control the school organization, including the business center.